Do Marketing Strategy, Product Characteristics, and Brand Affect The Sale of Zara Fashion Products? - Senjawati, Vita; Setiasih , Setiasih; Dandono, Yustinus Rawi (Asean International Journal of Business, 2024)
Aim - The goals of this paper are to ascertain whether marketing strategy, product characteristics, and brand have a partial effect on sales of ZARA products and whether marketing strategy, product characteristics and brand have a simultaneous effect on ZARA product sales. Methodology/approach - This study employs quantitative methods, with non-probability sampling and the purposive sampling technique. The analysis technique using a computer program SPSS 24.0 and data collection is accomplished through the distribution of online questionnaires. The number of respondents in this study was 100, they were taken in Petukangan, The data was analyzed using the Slovin formula with a (e) 5% error rate, multiple linear regression analysis, the coefficient of determination (R2), t test, and F test. Findings – If the marketing strategy, product characteristics, and brand are increased by one unit, sales will increase by 15.2%, marketing strategy 17.7%, product characteristics 21.3% as partially as brand has greater effect and is more significant on sales. As partially, brand has the greatest impact and significance on sales, followed by marketing strategies and finally product characteristics, while simultanously showed that the independent variable